Pemberdayaan Ekonomi Masyarakat Melalui Kelompok Tani - Abdul Yami; Dindin Solahudin; Dedi Herdiana (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2021)
The objectives of this study are: First, to describe the strategy of a prosperous farmer group in improving the economy of the community in the Cikadut Village. Second, to identify the process of empowering prosperous farmer groups in improving the economy of the community in Cikadut Village; Third is to measure the success rate of prosperous farmer groups in the economic field in the Cikadut Village. This study uses descriptive methods, the type of data used is negative, the data sources used are primary and also secondary data while the data collection techniques used in the study are observation, interview, and documentation study. From the results of this study indicate that: First, with the existence of farmer groups make the economic well-being of the community which the majority of the income from agricultural produce is more prosperous. Second, In the process economic empowerment through prosperous farmer groups has stages including: Engagement, Assessment, Action and Facilitation. Third, at least every month the people who are members of the Prosperous Farmers group have income, which is generated from the sale of the harvest or processed products from the harvest.